2018
DOI: 10.1159/000490139
|View full text |Cite
|
Sign up to set email alerts
|

Dual Delivery of bFGF- and NGF-Binding Coacervate Confers Neuroprotection by Promoting Neuronal Proliferation

Abstract: Background/Aims: Basic fibroblast growth factor (bFGF) and nerve growth factor (NGF) are essential for proper development, survival, growth, and maintenance of neurons in the central and peripheral nervous systems. However, because bFGF and NGF have short half-life and rapid diffusion rate, they have limited clinical efficacy. Thus, there is an urgent need to develop an effective delivery system to protect bFGF and NGF from proteolysis while maintaining their normal bioactivities. Methods: To more efficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In the present study, we either knocked down bFGF or administered OGD to induce morphological and cell viability changes of cultured rat neurons. We found OGD could induce swollen cell bodies and shortened axon length, which was consistent with numerous evidence that OGD treatment could deteriorate the growth of neurons (He et al, 2016;Lin et al, 2015;Liu, Yang, Tian, & Ma, 2016;Wang, Liang, et al, 2014;Wu et al, 2018;Zhang et al, 2014) and it could result in neural damage (Kusumoto et al, 1997;Li, Suo, Liu, Li, & Xue, 2017). Further, we confirmed that bFGF-siRNA had a passive effect on the growth and normal morphology of neurons.…”
Section: Bfgf Plays a Neuroprotective Role In Cultured Primary Cortex Neuronssupporting
confidence: 91%
“…In the present study, we either knocked down bFGF or administered OGD to induce morphological and cell viability changes of cultured rat neurons. We found OGD could induce swollen cell bodies and shortened axon length, which was consistent with numerous evidence that OGD treatment could deteriorate the growth of neurons (He et al, 2016;Lin et al, 2015;Liu, Yang, Tian, & Ma, 2016;Wang, Liang, et al, 2014;Wu et al, 2018;Zhang et al, 2014) and it could result in neural damage (Kusumoto et al, 1997;Li, Suo, Liu, Li, & Xue, 2017). Further, we confirmed that bFGF-siRNA had a passive effect on the growth and normal morphology of neurons.…”
Section: Bfgf Plays a Neuroprotective Role In Cultured Primary Cortex Neuronssupporting
confidence: 91%
“…The bioactivity of the released NGF from the NGF‐BCT22 was assessed in vitro using PC12 cells co‐cultured with the NGF releasing BCT22. PC12 cells are commonly used to assess NGF bioactivities in vitro since they change phenotype and develop characteristics similar to sympathetic neurons in the presence of NGF in a dose dependent fashion (Das, Freudenrich, & Mundy, ; Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…PC12 and SH-SY5Y cells were used to test the suitability of the system. The group containing bFGF and NGF promoted cell growth and proliferation better than those containing only bFGF or NGF [ 86 ].…”
Section: Discussionmentioning
confidence: 99%